Localization of the 5‐hydroxytryptamine 4 receptor in equine enteric neurons and extrinsic sensory fibers. Issue 7 (3rd March 2017) - Giancola, F.; Rambaldi, A. M.; Bianco, F.; Iusco, S.; Romagnoli, N.; Tagliavia, C.; Bombardi, C.; Clavenzani, P.; De Giorgio, R.; Chiocchetti, R.
Abstract: Background: Serotonin plays a pivotal role in regulating gut motility, visceral sensitivity, and fluid secretion via specific receptors. Among these receptors, 5‐HT4 exerts a prominent control on gut motor function. Although the prokinetic effect exerted by 5‐HT4 agonists is well known, the cellular sites of 5‐HT4 expression remain poorly understood in large mammals, e.g., horses. In this study, we evaluated the distribution of 5‐HT4 in the horse intestine and in foals with enteric aganglionosis, reminiscent of human Hirschsprung's disease. Methods: The intestine and spinal ganglia were obtained from three healthy horses and two foals with hereditary ileocolonic aganglionosis. Tissues were processed for immunohistochemistry using a specific antibody to 5‐HT4 and a variety of neuronal markers. Myenteric and submucosal plexus 5‐HT4 ‐immunoreactive (IR) neurons were quantified as relative percentage (mean±SD) to the total number of neurons counted. Furthermore, the density of 5‐HT4 ‐IR nerve fibers was evaluated in the mucosa and tunica muscularis . Key Results: The 5‐HT4 immunoreactivity was localized to large percentages of myenteric neurons ranging from 28±9% (descending colon) to 63±19% (ileum), and submucosal neurons ranging from 54±6% (ileum) to 68±14% (duodenum). The 5‐HT4 ‐immunoreactivity was co‐expressed by some substance P‐IR (SP‐IR) spinal ganglion neurons and extrinsic sensory fibers of aganglionic foals. Conclusions & Inferences: The presence of 5‐HT4 in many enteric and extrinsic sensory neurons and nerve fibers provides solid morphological evidence of the cellular sites of 5‐HT4 expression in horses. The evidence of SP‐IR sensory neurons positive for 5‐HT4 suggests its role in visceral sensitivity. Abstract : The 5‐hydroxytryptamine 4 receptor (5‐HT4) exerts a prominent control on gastrointestinal functions. Morphological data describing its localization in the enteric nervous system of large mammals, including horses, are lacking. In healthy horses, 5‐HT4 was identified in some spinal ganglia neurons and large percentages of enteric neurons; in aganglionic foals, 5‐HT4 was localized in visceral extrinsic sensory fibers. Our results demonstrate that 5‐HT4 is widely expressed by different subsets of enteric neurons and by extrinsic visceral sensory fibers.